Testing of Usability and Correctness Aspects in Marketing and Ordering Information Systems - Masyora, Nabilah Faqita; Hartono, Nahrun; Rahman, Rahman (Intechno Journal : Information Technology Journal, 2024)
Purpose: This research systematically evaluates the quality of the web-based marketing and ordering information systems at UD. Percetakan Citra Satria by focusing on the aspects of usability and correctness, aiming to determine the effectiveness of the system in meeting user needs. Methods/Study design/approach: Data collection was conducted through observation and questionnaires. The observation aimed to identify issues during the use of the marketing and ordering information systems at UD. Percetakan Citra Satria, while the questionnaire, using a Likert scale, involved 8 employees and 70 customers to assess usability and correctness. The system was implemented and tested by allowing users to interact with it, with evaluations analyzed using the McCall model. The testing focused on usability, reflecting ease of use, and correctness, ensuring information accuracy, both critical for enhancing user experience and operational effectiveness. Result/Findings: The test results indicate that the overall quality of the web-based marketing and ordering information systems at UD. Citra Satria Printing achieved a score of 85% for the usability aspect and 85.3% for correctness. These scores are classified as very good according to the quality factor percentage scale. Novelty/Originality/Value: This study introduces novelty in applying quality testing for a web-based marketing and ordering information systems using the McCall method, focusing on two main aspects: usability and correctness. The novelty lies in its specific application context, namely in the printing industry (UD. Percetakan Citra Satria), as well as the use of questionnaires to directly incorporate the perspectives of employees and customers.